Early Life Exposure to Chronic Intermittent Hypoxia Primes Increased Susceptibility to Hypoxia-Induced Weakness in Rat Sternohyoid Muscle during Adulthood - McDonald, Fiona B.; Dempsey, Eugene M.; O'Halloran, Ken D. (Frontiers in Physiology, 2016)
Intermittent hypoxia is a feature of apnea of prematurity, chronic lung disease and sleep apnea. Despite the clinical relevance, the long-term effects of hypoxic exposure in early life on respiratory control are not well defined. We recently reported that exposure to chronic intermittent hypoxia (CIH) during postnatal development (pCIH) causes upper airway muscle weakness in both sexes, which persists for several weeks. We sought to examine if there are persistent sex-dependent effects of pCIH on respiratory muscle function into adulthood and/or increased susceptibility to re-exposure to CIH in adulthood in animals previously exposed to CIH during postnatal development. We hypothesized that pCIH would cause long-lasting muscle impairment and increased susceptibility to subsequent hypoxia. Within 24 hours of delivery, pups and their respective dams were exposed to CIH: 90s of hypoxia reaching 5% O2 at nadir; once every 5 min, 8 hrs per day for 3 weeks. Sham groups were exposed to normoxia in parallel. Three groups were studied: sham; pCIH; and pCIH combined with adult CIH (p+aCIH), where a subset of the pCIH-exposed pups were re-exposed to the same CIH paradigm beginning at 13 weeks. Following gas exposures, sternohyoid and diaphragm muscle isometric contractile and endurance properties were examined ex vivo. There was no apparent lasting effect of pCIH on respiratory muscle function in adults. However, in both males and females, re-exposure to CIH in adulthood in pCIH-exposed animals caused sternohyoid (but not diaphragm) weakness. Exposure to this paradigm of CIH in adulthood alone had no effect on muscle function. Persistent susceptibility in pCIH-exposed airway dilator muscle to subsequent hypoxic insult may have implications for the control of airway patency in adult humans exposed to intermittent hypoxic stress during early life.